2010
DOI: 10.1007/s11999-009-1058-5
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Clinical Significance of Acromial Spur in Rotator Cuff Tear: Heel-type Spur and Rotator Cuff Tear

Abstract: Acromial spurs reportedly relate to the impingement syndrome and rotator cuff tears. We classified the morphologic characteristics of the acromion (shape and thickness) and acromial spurs and determined whether they correlated with rotator cuff tears. We measured acromial shape and thickness using simple radiography and MR arthrography or CT arthrography in 106 patients with full-thickness rotator cuff tears and in 102 patients without tears. Acromial spurs could be classified morphologically into six types: h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 21 publications
4
77
0
Order By: Relevance
“…1,2,23 One study showed that acromial spurs can be classified according to the distinct morphology and that the most common heel-type spur might be a risk factor for FTRCT. 25 In this study, heel-type spurs were most common and were detected in 19 shoulders (76%) in the PABST group, 169 shoulders (72.2%) in the FTRCT group, and 15 shoulders (71.4%) in the small FTRCT group.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…1,2,23 One study showed that acromial spurs can be classified according to the distinct morphology and that the most common heel-type spur might be a risk factor for FTRCT. 25 In this study, heel-type spurs were most common and were detected in 19 shoulders (76%) in the PABST group, 169 shoulders (72.2%) in the FTRCT group, and 15 shoulders (71.4%) in the small FTRCT group.…”
Section: Discussionmentioning
confidence: 49%
“…Acromial spur formation and acromion shape are known to be related to subacromial impingement and rotator cuff tears. 2,23,25 We checked for acromial spurs on the coronal and sagittal planes with MRI 25 and found a higher frequency of coronal acromial spurs in the PABST group compared with the FTRCT group (P ¼ .021); however, this difference was not evident between the PABST group and the small FTRCT group. This could be one of the characteristics of PABST lesions, even though debate still exists regarding whether acromial spurs are a cause or consequence of rotator cuff tears.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximal width (mm) of inferiorly directed spurs was measured. Ossification of the coracoacromial ligament or presence of a sub-coracoacromial spur can be identified in the sagittal oblique plane [28,29] as well as on oblique coronal sequences [28]. To achieve a high level of comparability to the reference standard (conventional radiography), we used oblique coronal sequences for size measurements and illustration of subcoracoacromial spurs on MR images.…”
Section: Imaging Analysismentioning
confidence: 99%
“…Therefore, ultrasound of the shoulder is not performed in all MSK centres and can be associated with limitations including: 1) Dependence on operator experience and acoustic window; and 2) Limited reproducibility and standardization. MR and radiographs are more common today for diagnosis of shoulder disorders and sub-coracoacromial spur formation as they provide more consistent and accurate information, and they can provide three-dimensional images of the acromion, spur shapes as well as rotator cuff and labral disorders at the same time [27,28]. Patients with SAIS may benefit from the addition of SWMR to a standard shoulder imaging protocol as it offers additional anatomical information in three dimensions without radiation exposure, offers a comparable short acquisition time of 4.5 minutes, and enables visualization of not only spur formation but also other important features of SAIS simultaneously.…”
Section: Swmr For the Assessment Of Sub-coracoacromial Spurs In Patiementioning
confidence: 99%